EKSPLORASI PEMBELAJARAN MATEMATIKA TINGKAT SD DI ERA PANDEMI PADA DUSUN JOMBOK DESA SEMBUNGIN KECAMATAN BANCAR KABUPATEN TUBAN - Prima Ayu Rizqi Mahanani; Ika Wulan Junianti (Jurnal Riset Pembelajaran Matematika, 2021)
The time of the pandemic produces a shift in learning from offline to online, and it will pose a new challenge in learning, especially the mathematical lessons that the formulas, if students are given only tasks without being explained, will create new problems because not all parents know mathematics and technology, Specifically strict follower of muslim TPQ Ar-Rohman's parents in the jombok hamlet Sembungin village Bancar district Tuban regency. Purpose this research is expected to find a solution to the problem’s online study at Jombok hamlet with subject strict follower of muslim TPQ Ar-Rohman trough descriptive qualitative research, as for the problem that is found that is parents lack the understanding of the material, the boredom of learning, and the parents lack the mastery over the technology available, so that a course for elementary school with a peer tutoring model and it turns out that with the guidance children make more enthusiastic about learning math.